Ewolucja koncepcji narodu w węgierskiej polityce po 1989 roku - Kopyś, Tadeusz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2025)
Ewolucja węgierskiej koncepcji narodu jest naznaczona stopniowym przejściem od luźnej tożsamości politycznej i kulturowej, skupionej wokół monarchii i państwa, do bardziej etnicznie zdefiniowanej i językowo naznaczonej koncepcji narodu. W szczególności wiek XIX i XX odegrały kluczową rolę w definiowaniu węgierskiego nacjonalizmu, ze znacznym naciskiem na język węgierski, integralność terytorialną i suwerenność narodową. Obecnie naród węgierski jest definiowany zarówno przez silne poczucie ciągłości historycznej, jak i zaangażowanie w określony zestaw wartości kulturowych i politycznych, ale napięcie między nacjonalizmem a integracją europejską nadal kształtuje jego ewoluującą tożsamość. Rząd Orbána, szczególnie po 2010 r., opowiadał się za wizją „chrześcijańskich Węgier”, rozwijał kontakty z mniejszością węgierską w krajach sąsiednich i podkreślał zachowanie narodowych wartości i kultury w kontekście europejskim. Podczas gdy Orbán, pragmatycznie popiera członkostwo w UE, jego rząd jednocześnie krytykował instytucje UE za to, co określano jako nadmierne wkraczanie w wewnętrzne sprawy Węgier. The evolution of the Hungarian conception of nation is marked by a gradual shift from a loose political and cultural identity, centred around monarchy and state, to a more ethnically defined and linguistically marked conception of nation. In particular, the 19th and 20th centuries played a key role in defining Hungarian nationalism, with a significant emphasis on the Hungarian language, territorial integrity and national sovereignty. The aim of this article is to analyse how the concept of nation has been shaped and evolved in Hungary after the political transition, since 1989. The analysis focuses on comparisons of politicians’ statements and legal acts influencing the formation of the concept of nation. The focus is on the emergence and characteristics of a new vision of the Hungarian nation at a crucial moment in Hungary’s regaining of sovereignty and pursuit of integration with the European Union, as well as in the unique situation of the Hungarian nation (a large Hungarian minority of approximately 5 million and a diaspora in European countries). Furthermore, the aim of the analysis is to try to find an answer who to the Hungarian nation in the circumstances of the breakdown of national unity in 1920 as a result of the Treaty of Trianon. It is also an attempt to present how national politics and national discourse changed not in Hungary after 1989. The subject has already been taken up many times by Hungarian researchers, but it is little known in Poland. We will also try to answer the question of what conception of the nation was tried to adopt in Hungary after the political transformation.
Evolution of the Concept of Nation in Hungarian Politics after 1989
Keywords: Węgry; diaspora poza granicami; polityka narodowa; koncepcja narodu; concept of nation; nationalism; Hungary; national minority; Hungarian diaspora